2018
DOI: 10.4269/ajtmh.17-0666
|View full text |Cite
|
Sign up to set email alerts
|

Serological Markers of Recent Campylobacter jejuni Infection in Patients with Guillain–Barré Syndrome in the State of Piauí, Brazil, 2014–2016

Abstract: In countries where poliomyelitis has been eradicated, Guillain-Barré syndrome (GBS) is the leading cause of acute flaccid paralysis. The range of infections that precede GBS in Brazil is unknown. infection is the most frequent trigger of GBS worldwide. Given the lack of systematic surveillance of diarrheal diseases, particularly in adults, the incidence of enteritis caused by in developing countries is unknown. From 2014 to 2016, pretreatment serum samples from 63 GBS patients were tested by immunoglobulin M (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Studies on GBS in Brazil outside of the ZIKV pandemic are scarce, and other infections have rarely been tested. 58,59 These results indicate that, as in other countries, C jejuni is the most common trigger in Brazil. The two patients with a recent DENV infection also had evidence of another infection: one with C jejuni and one with CMV.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Studies on GBS in Brazil outside of the ZIKV pandemic are scarce, and other infections have rarely been tested. 58,59 These results indicate that, as in other countries, C jejuni is the most common trigger in Brazil. The two patients with a recent DENV infection also had evidence of another infection: one with C jejuni and one with CMV.…”
Section: Discussionsupporting
confidence: 62%
“…Raw data were was clustered based on a distance matrix using Pearson's correlation and hierarchical cluster algorithm, and clipped at a 10 000 upper limit patients (75%) were able to walk unaided at 6 months. The five patients with a M pneumoniae infection were frequently <18 years old (2/5, 40%), and had a relatively long time between antecedent event and onset of weakness(18)(19)(20)(21)), and a high MRC sum score at entry(59)(60)), and 2/2 reported patients had fully recovered at 8 weeks. The patient with a recent EBV infection was 9 years old, and had preceding symptoms of headache and nausea, a sensorimotor demyelinating variant, and full recovery of disability at 13-week follow-up.…”
mentioning
confidence: 99%
“…We reviewed 135 full-text articles, of which 31 were eligible for inclusion ( Fig 1). Of the 31 studies, 28 reported countryspecific GBS rates from 13 LAC countries (Tables 1 & 2), 3 regional rates, [18,35,36] 15 background rates [18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48], 11 rates during an arboviral outbreak [49][50][51][52][53][54][55][56][57][58][59], and 5 compared rates before and during an outbreak [27,[60][61][62][63]. Many studies presented data from Brazil (29%) and Colombia (16%), and the majority (68%) were published in 2015 or later.…”
Section: Resultsmentioning
confidence: 99%
“…In Veracruz, Mexico, 75% of GBS patients tested positive for C. jejuni infection in 2017 (after the peak of ZIKV) [49]. Studies in Aruba, Brazil, and Colombia-all except the one from Aruba were conducted during the ZIKV epidemic-found no association between C. jejuni infection and GBS [43,46,50,52,55,58]. A study in Brazil found respiratory infections to be present in 27% of GBS patients compared to 7% with gastrointestinal infections in pre-ZIKV years (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Aruba, Brazil, and Colombia–all except the one from Aruba were conducted during the ZIKV epidemic–found no association between C . jejuni infection and GBS [43, 46, 50, 52, 55, 58]. A study in Brazil found respiratory infections to be present in 27% of GBS patients compared to 7% with gastrointestinal infections in pre-ZIKV years (1995–2002) [43].…”
Section: Discussionmentioning
confidence: 99%